Reflecting upon PAS - Arkesteijn, Monique (A+BE | Architecture and the Built Environment, 2019)
By now, the PAS design decision method is familiar and it is known that: 1 The Preference-Based Design procedure could be adapted and implemented into an accommodation strategy formation project so that it can be used at real estate portfolio level in CRE alignment process (see chapter 4); 2 The stakeholders were able to perform all PAS design decision steps and accepted the outcome (see chapter 5 and 6); 3 The facilitator and the systems engineers were able to represent the pilots in mathematical decision models (see chapter 7), and; 4 The stakeholders evaluated PAS design decision method positively (see chapter 8). In paragraph 9.1 it is shown that the PAS design decision method can be used as add-on to current CRE alignment management models. However, using the PAS method as add-on in these models creates managerial and methodical difficulties. The structure of these models is often not congruent with the structure of the PAS method (see chapter 2). An add-on of the PAS method in an alignment model does not fit well. To avoid these difficulties in the pilot studies a specific CRE alignment management system is set up which is congruent with the PAS design decision system: the PAS design decision management system. The PAS design decision method has been structured from a decision making perspective around Kickert’s three rationalities (components) (in De Leeuw, 2002). To complete PAS, PAS is described solely as design method in paragraph 9.2. In paragraph 9.3 the PAS management system is structured from a systems’ management perspective. From this perspective the three components can be described from the organizations’ point of view as well as the CRE manager and facilitator that executes PAS. Management as such is seen as steering in this thesis as is explained in chapter 3. PAS management system is defined based on a systems perspective as following the chosen basic concepts and definitions as explained in paragraph 3.1.14 and 3.1.15.